Latent Tuberculosis Infection Testing Practices in Long‐Term Care Facilities, Boston, Massachusetts. Issue 6 (3rd May 2017) - Reddy, Divya; Walker, Jacob; White, Laura F.; Brandeis, Gary H.; Russell, Matthew L.; Horsburgh, Charles R.; Hochberg, Natasha S.
Abstract : Objectives: To describe latent tuberculosis infection (LTBI) testing practices in long‐term care facilities (LTCFs). Design: Retrospective cohort study. Setting: Three Boston‐area LTCFs. Participants: Residents admitted between January 1 and December 31, 2011. Measurements: Resident demographic characteristics, comorbidities, LTCF stay, and LTBI testing and treatment. Results: Data for 291 LTCF residents admitted in 2011 were reviewed. Of the 257 without a history of LTBI and with documentation of testing, 162 (63%) were tested; 114 of 186 (61%) with a stay less than 90 days and 48 of 71 (68%) with a stay of 90 days or longer were tested. Of 196 residents with data on prior LTBI testing, 39 (19.9%) had LTBI; 12 of these (30.8%) were diagnosed at the LTCF. Hispanic participants were more likely than black participants to undergo LTBI testing (adjusted odds ratio (aOR) = 2.4, P = .003). Having a length of stay of less than 90 days (aOR = 0.7, P < .001) and history of illicit drug use (aOR = 0.7, P < .001) were associated with lower odds of LTBI testing. Conclusion: One‐fifth of LTCF residents had LTBI, but testing was not always performed. The high prevalence of LTBI in older adults combined with the risk of an outbreak if a case of tuberculosis occurs in a LTCF make LTBI testing and treatment an important prevention opportunity. The importance of LTBI testing in LTCFs needs to be reinforced.